(Ser)tão diplomático: por uma história da memória do cangaço em Limoeiro do Norte – CE (1977-2017) - Brito, Benedito Renan Bezerra de (2024)
This study investigates memory as a dynamic historical process in constant transformation, focusing on the history of the memory of "cangaço" (banditry in the Brazilian Northeast) and on how the city of Limoeiro do Norte, in Ceará, manages and reinterprets the memories associated with Lampião’s brief visit in 1927. This event, captured in photographs and covered by the Ceará press, underwent processes of forgetting, remembrance, and reinterpretation, ultimately establishing itself as a public memory with cultural and identity functions. This construction occurs through narratives of local social groups and families who, across generations, reinterpret the past using various forms of transmission, including orality, writing, and public spaces. The research analyzes the mechanisms of maintenance, preservation, and forgetting involved in these narratives, reflecting on the appropriations and representations of the "cangaço" by Limoeiro memorialists and questioning the memory frameworks to understand the re-elaborations and uses of this past by local elites. The analysis of the periods of remembrance and commemoration of Lampião's visit helps to understand the role of various social and cultural agents in constructing a local identity forged through the practices of evoking these memories. The results point to the formation of a "diplomatic (Ser)tão," shaped by the practices of remembrance and reinterpretation of the "cangaço" memories, highlighting a complex process of identity construction and a dynamic of preservation and transformation of collective memory.